Advantages and Requirements in Time Resolving Tracking for Astroparticle Experiments in Space - Matteo Duranti; Valerio Vagelli; Giovanni Ambrosi; Mattia Barbanera; Bruna Bertucci; Enrico Catanzani; Federico Donnini; Francesco Faldi; Valerio Formato; Maura Graziani; Maria Ionica; Lucio Moriconi; et al. (Instruments, 2021)
A large-area, solid-state detector with single-hit precision timing measurement will enable several breakthrough experimental advances for the direct measurement of particles in space. Silicon microstrip detectors are the most promising candidate technology to instrument the large areas of the next-generation astroparticle space borne detectors that could meet the limitations on power consumption required by operations in space. We overview the novel experimental opportunities that could be enabled by the introduction of the timing measurement, concurrent with the accurate spatial and charge measurement, in Silicon microstrip tracking detectors, and we discuss the technological solutions and their readiness to enable the operations of large-area Silicon microstrip timing detectors in space.